Recognizing peripheral ecosystems in marine protected areas: A case study of golden jellyfish lakes in Raja Ampat, Indonesia. (February 2020) - Maas, Diede L.; Capriati, Agustin; Ahmad, Awaludinnoer; Erdmann, Mark V.; Lamers, Machiel; de Leeuw, Christiaan A.; Prins, Luca; Purwanto; Putri, Amanda P.; Tapilatu, Ricardo F.; Becking, Leontine E.
Abstract: Peripheral marine ecosystems can harbor endemic diversity and attract tourism attention, yet are generally not included in conservation management plans due to their remoteness or inland positioning. A case study in Raja Ampat of seven landlocked marine lakes containing golden jellyfish ( Mastigias spp.) was conducted to address the lack of fundamental insights into evolutionary, ecological and social contexts of these ecosystems. An interdisciplinary approach was taken towards identifying the jellyfish lakes as distinct management units in order to incorporate them into existing Marine Protected Areas. Mastigias papua populations showed strong genetic (ϕST : 0.30–0.86) and morphological (F = 28.62, p -value = 0.001) structure among lakes, with putative new subspecies. Risks arising from rapid increase in tourism to Raja Ampat (30-fold since 2007) warrant restrictions on jellyfish lake use. Recommendations are provided for adaptive management and science-based conservation policies for jellyfish lakes across Indonesia. Graphical abstract: Unlabelled Image Highlights: Effective conservation in peripheral marine ecosystems mostly lacking Case study on jellyfish lakes in Raja Ampat to identify management units (MU) Genetic, morphological and stakeholder data indicate each jellyfish lake as MU Tourism pressure and other threats warrant consideration of redefining MPA zonation Recommendations for adaptive management of peripheral marine ecosystems